Transformational Leadership on Organizational Performance through Variations of Work Methods in National Logistics Companies - Devi Marlita; Okin Ringan Purba; Melia Dianingrum (Dinasti Publisher, 2024)
This study aims to provide a better understanding of how transformational leadership and variations of work methods can be used effectively in the logistics industry, as well as provide practical guidance for leaders and managers to improve the performance of their organizations. The research design in this study generally adopts a quantitative research approach. It is an explanatory study that aims to test all proposed hypotheses, building on previous research and literature. In addition, this study seeks to explain the relationship and influence between research variables (transformational leadership, and variations in work methods with organizational performance). Furthermore, the sampling method used in this study is non-probability sampling, which is considered capable of providing valuable and reliable insights to obtain potential information. The sampling design uses a purposive sampling approach, namely the selection of samples based on certain criteria. Based on the results of hypothesis testing, it can be concluded that there is no significant relationship between Transformational Leadership and Variations in Work Methods. There is no significant relationship between Variation of Work Methods and Organizational Performance. Although there is no significant relationship in this test, this does not mean that the relationship between the variables does not exist at all. Other factors not measured in this study may influence the relationship between Transformational Leadership, Variation of Work Methods, and Organizational Performance.